Strain-induced fully coherent triphase nanoarchitecture in refractory high-entropy alloys - Yu Zhang; Zhiqiao Li; Jin Xie; Xiaojun Zhao; Houwen Chen; Yunzhi Wang; Jian-Feng Nie (Science, 2026)
Nanostructured materials have exceptional properties, yet scalable fabrication of bulk, three-dimensional, nanograined structures remains a formidable challenge. We report the self-assembly of a fully coherent, triphase nanostructure—resembling a mesocrystal—formed through solid-state phase separation in an equiatomic refractory alloy. The resulting architecture integrates three common metallic crystal structures—face-centered cubic, body-centered cubic, and hexagonal close-packed—interwoven through strain-induced phase separation and unconventional transformation pathways triggered by the separation itself. This nanostructure accommodates large atomic-size mismatches and lattice misfits while maintaining full coherency and thermal stability. The resulting material exhibits a compressive yield strength exceeding 2 gigapascals. These findings provide a method for nanostructure engineering in compositionally complex alloys through strain-induced transformation pathway engineering.